Characteristics of women who practice yoga in different locations during pregnancy. Issue 8 (21st August 2015) - Cramer, Holger; Frawley, Jane; Steel, Amie; Hall, Helen; Adams, Jon; Broom, Alex; Sibbritt, David
Abstract : Objectives: Yoga practice during pregnancy is gaining increasing popularity. This study examined the characteristics of pregnant women who practiced yoga in regard to the different locations (at home, in yoga classes, or both). Design: The study sample was drawn from the Australian Longitudinal Study on Women's Health (ALSWH), a national longitudinal study of women to investigate multiple factors affecting health and well-being of women over a 20-year period. Setting: Postal survey. Participants: Women born between 1973 and 1978, who were randomly selected from the national Medicare database and identified as being pregnant or having recently given birth (n=2316). Outcome measures: Relationships between yoga use (attending yoga classes and/or practising yoga at home) and women's characteristics (demographic measures, pregnancy-related health concerns, health service utilisation, attitudes to complementary and alternative medicine). Results: Practising yoga both at home and in classes was associated with perceiving complementary and alternative medicine (CAM) as preventative (odds ratio (OR)=1.62); perceiving CAM as affording health control (OR=1.50); experiencing sadness (OR=1.72); preparing for labour (OR=2.31); birthing in a birth centre (OR=7.97); and experiencing less vomiting (OR=0.38). Practising at home only was associated with perceiving CAM as affording health control (OR=1.76); perceiving CAM as promoting a holistic health approach (OR=1.65); and birthing in a birth centre (OR=3.54). Practising in classes only was associated with experiencing stress (OR=1.97); and birthing in a birth centre (OR=4.85) (all p<0.05). Conclusions: The findings suggest that the location in which a woman practices yoga is associated with attitudinal, health-related and birth environmental factors.